Unpacking social dynamics of stress tolerant rice variety (STRV) seed systems - Mohan, Rohini Ram (International Rice Research Institute, 2018)
Presented by Rohini Ram Mohan (IRRI), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.